(untitled) (Research, Society and Development, 2023)
Application of ultrasound pretreatment in obtaining pequi pulp oil (Caryocar brasiliense Camb.) by cold pressing was evaluated concerning yield, quality of the oil obtained, mainly in relation to carotenoid and fatty acid compositions, and oxidative stability. There was an increase of approximately 11% in the process yield compared to the cold pressing without ultrasound pretreatment. The application of ultrasound pretreatment increased the amount of total carotenoids (about 1.5 times) in the oil and modified the composition of the carotenoids present. Furthermore, there was an increase in oil unsaturation. Ultrasound application did not interfere negatively on the oxidative stability of the oil with respect to heat and light after 20 days of storage. Oils with ultrasound pretreatment had a higher carotenoid retention until 10 days of storage and reached peroxide indices 2.6 times lower than samples without pretreatment after 20 days of exposure to light.